Pengaruh Kepemimpinan Kepala Sekolah terhadap Pembelajaran Organisasional dan Dampaknya pada Perilaku Positif Calon Pendidik Ekonomi - Djatmika, Ery Tri (Universitas Brawijaya, Indonesia, 2009)
In a tight competition climate among organizations, it is expected that each institution is able to provide excellent service to its customers. In a context of education institution, educators have important roles in developing students' competencies either academically through delivering teaching learning process or through other non-academic activities. To be able to work effectively, they need to have extra-role behaviors. It means that they have to pay attention to students, colleagues, and school organization. In this research, hypothetically, principal leadership is examined as an antecedent variable to organizational learning and its impact to extra-role behavior. Survey was conducted to economic education students who were taking field internship program at schools. Structural equation modeling was employed to analyze casual relationship among variables investigated. Research findings revealed that principal leadership has direct effect to organizational learning and indirect effect to extra-role behavior.